2016
DOI: 10.12930/nacada-16-014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Technology-Mediated Communication on Student Evaluations of Advising

Abstract: The field of academic advising lags behind other similar fields in the use of technologically mediated communication modalities shown to improve academic outcomes. We investigated student satisfaction with undergraduate advising by examining the ways communication methods, such as social media, between student and advisor relate to student satisfaction. Results showed that although advisors rarely communicated with students via social media, text messaging, or instant messaging, the number of face-to-face advi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The results of the analysis for the third hypothesis are accepted, which means that peer interaction plays a certain role in students' employability. This finding supports the results of previous studies, which found that peer interactions are responsible for employee employability [49]. Interaction with peers enables ISSN: 2252-8822 …”
Section: Regression Analysis Testsupporting
confidence: 91%
“…The results of the analysis for the third hypothesis are accepted, which means that peer interaction plays a certain role in students' employability. This finding supports the results of previous studies, which found that peer interactions are responsible for employee employability [49]. Interaction with peers enables ISSN: 2252-8822 …”
Section: Regression Analysis Testsupporting
confidence: 91%
“…Service innovations in higher education range from moving processes online, to developing and deploying mobile apps, to developing self-service applications that enable students to make degree plans tied to career objectives, to facilitating up-to-date communications between students and academic advisors. While from an outsider perspective, the above might not appear to be innovations, given the technology developments in our broader economy and how this has shaped students' expectations for e-services [30], including a strong dissatisfaction with student-facing technology [32], the above are indeed novel in many higher education institutions [34] and as such constitute "innovations" [35].…”
Section: Importance Of Research Topicmentioning
confidence: 99%
“…does not occur in real time (Amador & Amador, 2013). However, more recently, the use of synchronous communication technology (happening in real time) has become increasingly useful for maintaining the student-advisor interaction, especially after COVID-19 necessitated a move to almost entirely remote teaching, learning and service in higher education (Argüello & Méndez, 2019;Gaines, 2014;Henderson & Goodridge, 2015;Junco et al, 2016). This includes using platforms like Zoom, MS Teams and Google Meets as examples of synchronous communication technology for advising.…”
Section: Literature Reviewmentioning
confidence: 99%